2005
DOI: 10.1200/jco.2005.01.8010
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Treatment of Cancer-Associated Anorexia and Weight Loss

Abstract: The optimal dose, time to start, and duration of treatment for many appetite stimulants for cancer anorexia is still unknown. A more systematic approach to research methodology with universal outcome measure and prospective randomized studies are need. Combination regimens are needed but this cannot at the present time be supported by the data presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
120
0
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(136 citation statements)
references
References 56 publications
3
120
0
13
Order By: Relevance
“…They include mainly appetite stimulants and anabolic agents such as prednisolone [15,51] and progesterone [12,42,43,77] and ghrelin, a ligand which stimulates growth hormone release [44,59]. Anecdotally, the use of α-3 omega fatty acids (eicosapentaenoic acid) [52] and thalidomide (potent anti-TNF activity) have been reported [48].…”
Section: Discussionmentioning
confidence: 99%
“…They include mainly appetite stimulants and anabolic agents such as prednisolone [15,51] and progesterone [12,42,43,77] and ghrelin, a ligand which stimulates growth hormone release [44,59]. Anecdotally, the use of α-3 omega fatty acids (eicosapentaenoic acid) [52] and thalidomide (potent anti-TNF activity) have been reported [48].…”
Section: Discussionmentioning
confidence: 99%
“…Central mechanisms accounting for dwindling appetite include fatigue, inflammatory signals mediated by cytokines, and hormonal, autonomic, and neuromediator imbalances. [28][29][30] Other comorbidities, including depressive symptoms, psychological distress, social withdrawal, and nausea, can further contribute to this problem. Hunger displays a strong circadian rhythm.…”
Section: Anorexia In Cancer Patientsmentioning
confidence: 99%
“…There are few pharmacological treatment options for CACS, but it has been shown that this patient population with advanced cancer has the capacity to respond to appetite stimulation therapy (Yavuzsen et al, 2005).…”
mentioning
confidence: 99%